The Effect Of Using Think Pair Share Stragey On Students’ Writing Ability In Descriptive Text At Seventh Grade Students Of Junior High School - Merisa Fauziah; Veni Roza; Reflinda Reflinda; Syahrul Syahrul (Jurnal Pendidikan dan Sastra Inggris, 2023)
This study examined the effect of the think-pair-share strategy on seventh grade students at the junior high school in MtsS Ashhabul Yamin, Lasi Tuo's ability to write descriptive text. The background for this study was the students' difficulties with writing when learning English. First, most of the students did not understand well how to make a short paragraph. Second, many of the students had limited of vocabulary. Third, some of the students were difficult to writing the sentences that has the correct grammar. In this study, the researcher compared two classes using a quantitative method and a quasi-experimental research design. The sample of this study were junior high school students in the seventh grade at MTsS Ashhabul Yamin, Lasi Tuo, specifically 7.6 as the experimental class with 28 students and 7.9 as the control class with 27 students. The instrument of this research was writing test. The data was analyzed by using independent sample t-test and paired sample t-test in SPSS 22. The result of the research indicated that there was significant effect of students writing ability between the students who were taught by using think pair share strategy and without using think-pair-share strategy. It can be seen from the value of sig. (2-tailed) which was smaller than the alpha value (0,000<0,05). From the result of the data, it can be concluded that, using think pair share strategy gave significant effect of writing ability in descriptive text.